DOUBLE LAYER IMPEDANCE ANALYSIS ON THE ELECTRICAL IMPEDANCE MEASUREMENT OF SOLUTION USING A PARALLEL PLATE - Chomsin Sulistya Widodo; Didik R Santoso; Unggul P Juswono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2016)
This research discusses the principles of measuring the electrical impedance of a solution using parallel plate probe. The method used is by injecting an AC-current in the solution within the frequency range of 1Hz - 1MHz. The electrical impedance value plotted as a function of frequency. The results of the experiment showed that the electrical impedance of a solution could be measured correctly by using this method. The surface area of the probe, the distance between the probe, and the frequency of the injected AC-current, giving the measured impedance value changes significantly. This method also proved to be used to identify the value of the concentration of the sugar solution with relatively good accuracy. The experiment results demonstrate conformity with the existing theory